THE INFLUENCE OF QUINOA FLOUR ON THE PROPERTIES OF THE DOUGH IN THE PRODUCTION OF GLUTEN-FREE BREAD (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2026)
The choice of gluten-free raw materials, which will positively affect the properties of the dough, is an important task for scientists and technologists. In the process of searching for new ingredients to create innovative and natural gluten-free bread, it is worth paying special attention to the components that increase the elasticity of the dough, its nutritional and sensory properties. Raw materials that can be interesting in the production of gluten-free bread include pseudocereals, in particular, quinoa. The purpose of this study is to evaluate the effect of Quartet quinoa flour on dough properties in the production of gluten-free bread. 5 samples of bread from gluten-free raw materials were studied. Sample 1 was made from a mixture of gluten-free raw materials: rice flour, corn starch, psyllium, golden flax and maltose. In samples 2, 3, 4, 5, part of the corn starch was replaced with Quartet quinoa flour, selected by scientists of the Sumy National Agrarian University. Quinoa grains for making sample 3 were pre-infused in cold water to remove saponins. Quinoa for the production of samples 4, 5 was treated with water and ultrasound. To prepare the dough, leavening agent based on rice flour, Lactobacillus sanfranciscensis and Candida humilis was used as a leavening agent. The addition of quinoa flour led to a decrease in the acidity of the dough, which had a positive effect on the formation of the structure of the finished products. Also, a decrease in the mass fraction of moisture was observed in the dough samples with quinoa flour. Starch pasteurization under conditions of lower humidity contributed to the formation of dry, elastic bread pulp. According to organoleptic indicators, bread with the addition of Quartet quinoa flour had a pleasant nutty taste, white color, dry, elastic crumb and a thin golden-yellow crust. The crumb of the bread samples with quinoa flour had a more uniform small thin-walled porosity, without cavities and signs of non-brewing, tempering. Sample 2, which contained unprocessed quinoa grains, showed slight bitterness. A sample made with a higher cornstarch content, without quinoa flour, had unsatisfactory organoleptic parameters.
Keywords: gluten-free bread; quinoa; dough; acidity; organoleptic properties